Systematic Review of Digital Literacy in the Implementation of Indonesian Language Learning - Septiari, Wahyu Dini; Suwandi, Sarwiji (Green Publisher Indonesia, 2024)
This research aims to collect, summarize, analyze, and synthesize information about digital media in learning from journal articles published between 2020 and 2024. The researcher conducted a literature search on several online databases, including Crossref and Google Scholar. The selection process resulted in 30 articles for analysis. The research findings indicate that among various learning media discussed in the articles are ICT devices, e-learning, animated videos, social media, Canva applications, Google Sites, Google Docs, pop-up books, flip classrooms, and coding.